2018
DOI: 10.1093/jrr/rry089
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of intensity-modulated radiotherapy with three dose-fractionation regimens for localized prostate cancer

Abstract: We evaluated long-term outcomes of three protocols of intensity-modulated radiation therapy (IMRT) for localized prostate cancer. Between 2005 and 2014, 348 patients were treated with 5-field IMRT. The first 74 patients were treated with a daily fraction of 2.0 Gy to 74 Gy (low-risk prostate cancer) or 78 Gy (intermediate- or high-risk prostate cancer); then 101 patients were treated with 2.1-Gy daily fractions to 73.5 or 77.7 Gy. More recently, 173 patients were treated with 2.2-Gy fractions to 72.6 or 74.8 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
1
12
1
Order By: Relevance
“…The cumulative incidence of late ≥grade 2 GI complications was only 4.8% in our current study, whereas that after definitive RT ranged from 7% to 15% [19][20][21] . This may be because a lower dose of 64-70 Gy is usually used in SRT as compared with a dose of 76-80 Gy in definitive RT.…”
Section: Discussioncontrasting
confidence: 68%
“…The cumulative incidence of late ≥grade 2 GI complications was only 4.8% in our current study, whereas that after definitive RT ranged from 7% to 15% [19][20][21] . This may be because a lower dose of 64-70 Gy is usually used in SRT as compared with a dose of 76-80 Gy in definitive RT.…”
Section: Discussioncontrasting
confidence: 68%
“…Table 2 summarizes the clinical outcomes after IMRT, PBT and CIRT, along with a comparison of the efficacies and safety parameters. 8,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] PBT and CIRT outcomes in Japanese patients were reported recently in a multicenter collaborative clinical study. 37,38 Iwata et al reported long-term outcomes from a multi-institutional survey of PBT for prostate cancer carried out by the Japanese Radiation Oncology Study Group.…”
Section: Local Particle Beam Rt: Mainly In the 2000smentioning
confidence: 89%
“…Table summarizes the clinical outcomes after IMRT, PBT and CIRT, along with a comparison of the efficacies and safety parameters . PBT and CIRT outcomes in Japanese patients were reported recently in a multicenter collaborative clinical study .…”
Section: Scientific Statementsmentioning
confidence: 99%
“…For GU toxicity, Carvalho, et al made a systematic review and meta-analysis and reported around 28% of late GU toxicity at 12 months or more after EBRT [ 31 ]. Takemoto reported 7.9–12.4% of GU Grade ≥2 ratio at 6–10 years using IMRT in Japan [ 32 ]. For HDR+EBRT, Ishiyama et al reported 5- and 10-year accumulated rates of late Grade ≥2 GU toxicities were 16.7% and 26.7% in 3424 Asian patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%